Estimation of cold plasma outflow during geomagnetic storms. Issue 12 (1st December 2015) - Haaland, S.; Eriksson, A.; André, M.; Maes, L.; Baddeley, L.; Barakat, A.; Chappell, R.; Eccles, V.; Johnsen, C.; Lybekk, B.; Li, K.; Pedersen, A.; et al.
Abstract:  Low‐energy ions of ionospheric origin constitute a significant contributor to the magnetospheric plasma population. Measuring cold ions is difficult though. Observations have to be done at sufficiently high altitudes and typically in regions of space where spacecraft attain a positive charge due to solar illumination. Cold ions are therefore shielded from the satellite particle detectors. Furthermore, spacecraft can only cover key regions of ion outflow during segments of their orbit, so additional complications arise if continuous longtime observations, such as during a geomagnetic storm, are needed. In this paper we suggest a new approach, based on a combination of synoptic observations and a novel technique to estimate the flux and total outflow during the various phases of geomagnetic storms. Our results indicate large variations in both outflow rates and transport throughout the storm. Prior to the storm main phase, outflow rates are moderate, and the cold ions are mainly emanating from moderately sized polar cap regions. Throughout the main phase of the storm, outflow rates increase and the polar cap source regions expand. Furthermore, faster transport, resulting from enhanced convection, leads to a much larger supply of cold ions to the near‐Earth region during geomagnetic storms. Key Points: Cold ion outflow increases significantly during geomagnetic storms The observed increase in cold ion flux is a result of centrifugal acceleration Transport of ions of ionospheric origin to the plasma sheet increases during storms